Increased dicentric chromosome in peripheral lymphocytes is related to acute skin toxicity induced by radiotherapy in cancer patients - Minjie Li; Yu Gao; Lin Han; Ping Wang; Jie Li; Junhua Song; Shasha Du; Yunfei Zhang; Yumin Lyu (Radiation Medicine and Protection)
Objective: To investigate the impacts of radiotherapy (RT) on dicentric chromosomes in peripheral blood lymphocytes of cancer patients, in order to explore the relationship between dicentric chromosomes and RT-induced adverse reactions. Methods: A total of 33 cancer patients after postoperative RT in a tertiary hospital from October 2021 to May 2022 were enrolled in this study. These patients were grouped according to the grade of acute skin and marrow toxicities determined based on the scoring criteria for acute morbidity developed by the Radiation Therapy Oncology Group (RTOG). Peripheral blood samples were collected from each patient before and after RT, followed by whole-blood lymphocyte culture and chromosome analysis. Dicentric chromosomes were searched automatically using a high-throughput chromosome analysis system and were then confirmed manually. Finally, the relationships of the frequency of dicentric chromosomes (also referred to as the dic frequency) with acute skin and marrow toxicities were assessed. Results: After RT, the mean counts of white blood cells (WBCs), lymphocytes, and platelets significantly decreased, while the red blood cells (RBCs) and hemoglobin notably increased (P ​< ​0.001), while the dic frequency was elevated remarkably, significantly higher in patients with higher-grade (>1) acute skin toxicities compared to those with lower-grade (=1) acute skin toxicities (Z ​= ​−1.985, P ​= ​0.047). However, no significant relationship was observed between the dic frequency and acute marrow toxicity after RT (P ​> ​0.05). Logistic regression showed that radiosensitivity denoted by the post-RT dic frequency in peripheral blood lymphocytes produced insignificant impacts on the severity of RT-induced acute skin toxicities (P ​= ​0.060). Conclusion: The elevated dic frequency in peripheral blood lymphocytes of cancer patients with higher-grade acute skin toxicities suggests enhanced radiosensitivity of peripheral blood lymphocytes, which is associated with the occurrence of RT-induced adverse reactions.